Interlaboratorial validation of serodiagnosis of infectious diseases - Kleba, Lisboa (2020)
Parallel detection of antibodies with different specificity has many potential applications in epidemiological research, vaccine development and in the diagnosis of allergies, autoimmune and infectious diseases. Although ELISA-based tests are suitable for this purpose, available assays can be time consuming and require large quantities of both sample and reagents thus limiting their application for mass screening.